Evaluasi Tingkat Kesiapan Keamanan Informasi Menggunakan Indeks Keamanan Informasi (Indeks KAMI) Versi 4.0 pada Dinas Komunikasi dan Informatika Kota Bogor - Pratiwi, Hadiati Agus; Wulandari, Lily (Journal of Industrial Engineering & Management Research, 2021)
Communications and Informatics Office of Bogor Municipality is a government agency that has the task of assisting the Mayor of Bogor in carrying out Government Affairs in the field of Communication, Informatics, Statistics, and Encryption management that has implemented e-Government in its public services. The impact of the e-Government’s implementation in public services with the increasing communication and exchange of data electronically causes vulnerabilities in information and communication system transactions which greatly affect the quality and security of information, so that the management of information security becomes very important for the Communications and Informatics Office of Bogor Municipality. This research was conducted to determine the level of readiness of information security management at the Communications and Informatics Office of Bogor Municipality using the Information Security Index (KAMI Index) Version 4.0 according to the security aspects defined by the ISO/IEC 27001:2013 standard made by the National Cyber and Crypto Board (BSSN). by evaluating various areas that are the target of the application of information security through the interview process. The evaluation result of the Electronic System Category obtained value of 35 and included in the Strategic Category illustrating that the use of electronic systems is an integral strategic part in supporting ongoing work processes. The evaluation result of the five areas of information security obtained a total score of 395 at the Basic Framework stage with Maturity Levels I+ to II. Based on the evaluation results, recommendations are prioritized at the lowest maturity level, namely the Information Security Risk Management area so that in the next evaluation there can be an increase in the level of information security maturity until it reaches the expected maturity level according to ISO 27001 compliance standards, which is at level III.